PENINGKATAN MINAT BELAJAR MENGENAL ANGKA 1–20 MELALUI PERMAINAN ULAR TANGGA EDUKATIF SEDERHANA PADA ANAK TUNAGRAHITA RINGAN KELAS I SD DI SLB NEGERI 1 MAKASSAR - Nurandini; Sitti Kasmawati; Abdul Hadis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The issue addressed in this study is the low learning interest among first-grade students with mild intellectual disabilities at SLB Negeri 1 Makassar, particularly regarding the topic of recognizing numbers 1–20. The research questions are: (1) What was the level of learning interest regarding numbers 1–20 among first-grade students with mild intellectual disabilities at SLB Negeri 1 Makassar prior to instruction using a simple educational Snakes and Ladders game? (2) What was the level of learning interest regarding numbers 1–20 among these students after instruction using the simple educational Snakes and Ladders game? and (3) Was there an increase in learning interest regarding numbers 1–20 among these students following the implementation of the simple educational Snakes and Ladders game? The subjects of this study were first-grade elementary students with mild intellectual disabilities. Data collection techniques included observation and documentation. The results, obtained over eight sessions, indicate that the students' learning interest increased following the use of the simple educational Snakes and Ladders game. The study concludes that: 1) Prior to using the simple educational Snakes and Ladders game, the students' learning interest fell into the "poor" category; 2) Instruction using the simple educational Snakes and Ladders game made students more interested and active in the learning process; and 3) Following the use of the simple educational Snakes and Ladders game, the students' learning interest improved, reaching the "excellent" category.